Свет надежды: [стихи] / Надежда Опалихина ; [авт. предисл. Г. С. Микрюкова] - Опалихина Надежда (2013)
Экземпляры: ф.9 (20161109) / Инвентарный номер: 57203 / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: О-60 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5